The Language Divide: The Importance of Training in the Use of Interpreters for Outpatient Practice - Karliner, Leah S (Blackwell Science Inc, 2004)
PURPOSE: Provision of interpreter services for non-English-speaking patients is a federal requirement. We surveyed clinicians to describe their experience using interpreters. SUBJECTS AND METHODS: In this cross-sectional study we surveyed clinicians in three academic outpatient settings in San Francisco (N = 194) regarding their most recent patient encounter which involved an interpreter. Questions about the visit included type of interpreter, satisfaction with content of clinical encounter, potential problems, and frequency of need. Previous training in interpreter use, languages spoken, and demographics were also asked. Questionnaires were self-administered in approximately 10 minutes. RESULTS: Of 194 questionnaires mailed, 158 were completed (81% response rate) and 67% were from resident physicians. Most respondents (78%) were very satisfied or satisfied with the medical care they provided, 85% felt satisfied with their ability to diagnose a disease and treat a disease, but only 45% were satisfied with their ability to empower the patient with knowledge about their disease, treatment, or medication. Even though 71% felt they were able to make a personal connection with their patient, only 33% felt they had learned about another culture as a result of the encounter. Clinicians reported difficulties eliciting exact symptoms (70%), explaining treatments (44%), and eliciting treatment preferences (51%). Clinicians perceived that lack of knowledge of a patient's culture hindered their ability to provide quality medical care and only 18% felt they were unable to establish trust or rapport. Previous training in interpreter use was associated with increased use of professional interpreters (odds ratio [OR], 3.2; 95% confidence interval [CI], 1.4 to 7.5) and increased satisfaction with medical care provided (OR, 2.6; 95% CI, 1.1 to 6.6). CONCLUSIONS: Clinicians reported communication difficulties affecting their ability to understand symptoms and treat disease, as well as their ability to empower patients regarding their healthcare. Training in the use of interpreters may improve communication and clinical care, and thus health outcomes.